Influence of systemic strontium ranelate on the progression and as adjunctive therapy for the nonsurgical treatment of experimental periodontitis - Gusman, David Jonathan Rodrigues [UNESP]; Matheus, Henrique Rinaldi [UNESP]; Alves, Breno Edson Sendão [UNESP]; Ervolino, Edilson [UNESP]; de Araujo, Nathália Januario [UNESP]; Piovezan, Bianca Rafaeli [UNESP]; Fiorin, Luiz Guilherme [UNESP]; de Almeida, Juliano Milanezi [UNESP] (Medicina Oral, S.L., 2021)
Background: Strontium Ranelate (SR) presents overlapping osteoanabolic and anti-resorptive activity. However, the effects of SR on the progression of periodontitis through the alveolar bone and its potential applicability as adjunctive therapy to scaling and root planning remain poorly accessed. The aim of this study was to evaluate the effects of systemic (SR) both on the progression of experimental periodontitis (EP) and as adjunctive therapy to SRP. Material and Methods: Eighty male rats were divided into four groups (n=20): EP-PSS: EP induction and systemic administration of physiological saline solution (PSS); EP-SR: EP induction and systemic administration of SR; EPSRP/ PSS: EP induction, SRP and systemic administration of PSS; EP-SRP/SR: EP induction, SRP and systemic administration of SR. Seven days after ligature placement, SRP was performed in EP-SRP/PSS and EP-SRP/SR, as well as the systemic administration of either PSS or SR were initiated and continued until euthanasia in all groups. Animals were euthanized at 7 and 30 days after the beginning of the systemic treatments. Histological, histometric (percentage of bone in the furcation [PBF]) and immunohistochemical (tartrate-resistant acid phosphatase [TRAP], Osteocalcin [OCN] and leukocyte common antigen [CD 45]) analyses were performed. Data were statistically analyzed. Results: EP-SRP/PSS showed a significantly more organized pattern of the connective tissue and alveolar bone structure than EP-SRP/SR. EP-SR showed significantly higher PBF than EP-PSS, however, EP-SRP/PSS showed no difference with EP-SRP/SR at 30 days. Conclusions: SR reduced the alveolar bone loss in non-treated animals and presented no standout benefits over the conventional forms of treating EP.
Keywords: alveolar bone loss; periodontal disease; root planing; Strontium Ranelate